2016
DOI: 10.1080/03008207.2016.1182998
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin inhibits lipopolysaccharide-induced inflammation and extracellular matrix catabolism in rat intervertebral disc

Abstract: Intervertebral disc (IVD) degeneration contributes to most spinal degenerative diseases, while treatment inhibiting IVD degeneration is still in the experimental stage. Sesamin, a bioactive component extracted from sesame, has been reported to exert chondroprotective and anti-inflammatory effects. Here, we analyzed the anti-inflammatory and anti-catabolic effects of sesamin on rat IVD in vitro and ex vivo. Results show that sesamin significantly inhibits the lipopolysaccharide (LPS)-induced expression of catab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Interestingly, the top 5 enrichments of GO BP included response to lipopolysaccharide (GO BP:003249), negative regulation of cell proliferation (GO BP:0008285), and response to hypoxia (GO BP:0001666). Lots of literatures reported that lipopolysaccharide could induce inflammatory response of IVD; thus, the biological processes in response to lipopolysaccharide indicated an important role of inflammation in NPC senescence [43]. Besides, hypoxia and inflammation are two important characteristics of the environment of degenerated IVD [44]; thus, these results highlighted a vital role of a local environment in NPC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the top 5 enrichments of GO BP included response to lipopolysaccharide (GO BP:003249), negative regulation of cell proliferation (GO BP:0008285), and response to hypoxia (GO BP:0001666). Lots of literatures reported that lipopolysaccharide could induce inflammatory response of IVD; thus, the biological processes in response to lipopolysaccharide indicated an important role of inflammation in NPC senescence [43]. Besides, hypoxia and inflammation are two important characteristics of the environment of degenerated IVD [44]; thus, these results highlighted a vital role of a local environment in NPC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM produced by NP cells performs a vital role in the maintenance of disc physiology, and ECM degradation is a major feature of IVDD 38 . MMPs and ADAMTS are catabolic enzymes that degrade the ECM in IVDD 39 . Our data indicated that BBR could effectively inhibit ECM degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Since therapeutic approaches for IVDD remain limited, biological anti‐inflammatory approaches to IVD regeneration have gained increasing interest. In cases of refractory LBP due to IVDD, anti‐inflammatory and/or anti‐degenerative therapies such as cytokine inhibition may relieve pain and slow down the progression of the disease 22‐31 . Several studies indicated that cyclooxygenase‐2 (COX2) inhibitors can reduce the inflammatory response in different models 25‐27 .…”
Section: Introductionmentioning
confidence: 99%